The Influence of Visual Context on the Emergence of the Especial Skill of Free Throw in Basketball among Experienced and Low Experienced Players - Akram Kavyani; Behrouz Abdoli; Alireza Farsi (Vesnu Publications, 2016)
Introduction: When, as a result of a great amount of practice, a skill is performed significantly better than similar skills within the same class, it is called an especial skill. The goal of this study was the examination of the influence of visual context on the emergence of the especial skill of free throws in basketball among experienced and low experienced players. Materials and Methods: In the present study, 10 experienced and 10 low experienced basketball players took 150 shots from 5 different distances from the basket including the free throw line. The players took their shots in 3 different visual contextual conditions (light, one point lighting, and dark). The linear regression, one-sample t-test, and the curve linear regression were used to analyze the data. Results: The results of the linear regression analysis of the data of the 4 distances showed a significant negative relation between distance and performance accuracy in the experienced group (P < 0.05, r = -0.68). In addition, the result of dependent t-test showed that the experienced group only illustrated a superior performance from the free throw line when the visual context was light and one point lighting (P < 0.05), but their performance was not superior when the visual context was dark. In low experienced players, a negative linear relationship was observed between the different distances and their performance scores (P < 0.05, r = -0.41). Moreover, the results showed that the curve linear regression analysis fit the data of the experienced group better (P < 0.05, r = -0.70). Conclusion: These findings showed the role of visual information in the emergence of the especial skill effect in experienced individuals.